Hepatocyte-specific regulation of autophagy and inflammasome activation via MyD88 during lethal Ehrlichia infection - Teymournejad, Omid; Sharma, Aditya Kumar; Abdelwahed, Mohammed; Kader, Muhamuda; Ahmed, Ibrahim; Elkafas, Hoda; Ismail, Nahed (Frontiers in Immunology, 2023)
Hepatocytes play a crucial role in protein synthesis, metabolism, and the body's response to infection. Ehrlichia is an obligate intracellular bacterium that causes potentially life-threatening human monocytic ehrlichiosis (HME) characterized by an initial liver injury followed by sepsis and multi-organ failure. We previously showed that Ehrlichia induces liver damage via deleterious MyD88-dependent activation of CASP11 and inhibition of autophagy in macrophage. While macrophages are major target cells for Ehrlichia, the role of HCs in ehrlichiosis remains unclear. We investigated here the role of MyD88 signaling in HCs during infection with highly virulent Ehrlichia japonica, which causes severe liver damage and fatal ehrlichiosis in mice using primary cells from wild-type (WT) and MyD88-/- mice, along with pharmacologic inhibitors of MyD88 in a murine HC cell line. Similar to macrophages, MyD88 signaling in Ehrlichia-infected HCs led to deleterious CASP11 activation, cleavage of Gasdermin D, secretion of high mobility group box 1, IL-6 production, and inflammatory cell death, while controlling bacterial replication. Unlike macrophages, MyD88 signaling in Ehrlichia-infected HCs attenuated CASP1 activation but activated CASP3. Mechanistically, active CASP1/canonical inflammasome pathway plays a hepatoprotective role as it negatively regulates activation CASP3 in MyD88-/- HCs. Further, MyD88 promoted autophagy induction in HCs, which was surprisingly associated with the activation of the mammalian target of rapamycin complex 1 (mTORC1), a known negative regulator of autophagy. Pharmacologic blocking mTORC1 activation in E. japonica-infected WT, but not MyD88-/- HCs, resulted in significant induction of autophagy, suggesting that MyD88 promotes autophagy not only in an mTORC1-indpenedent manner, but also abrogates mTORC1-mediated inhibition of autophagy in HCs following E. japonica infection. Together, this study demonstrates that MyD88 mediated regulation of autophagy and canonical inflammasome pathway in HCs is distinct from MyD88 signaling in macrophages during fatal Ehrlichia infection. Understanding cell-specific signaling is critical for the development of new therapeutics against liver-targeting infectious diseases such as HME.